Starting a National Conversation: The Institute of Medicine Workshop on the Future Directions of Credentialing Research in Nursing. (January 2015) - Lundmark, Vicki
Abstract : In this month's column, the director of research for the American Nurses Credentialing Center discusses outcomes of the Institute of Medicine Workshop on Credentialing Research in Nursing. Abstract : Supplemental Digital Content is available in the text.